Method for producing a dry solid, and dry solid
Patent Information
- Application Number
- JP2025061949
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2025-04-03
- Publication Date
- 2026-10-16
AI Technical Summary
【0011】 本開示の製造方法により得られる乾燥固体又は本開示の乾燥固体を水と混合することにより、熱線吸収特性を有する複合体を水中で再分散させることができる。再分散された複合体は良好な熱線吸収特性を発揮することができる。
Smart Images

Figure 2026168659000001 
Figure 2026168659000002 
Figure 2026168659000003
Abstract
Description
Technical Field
[0001] The present disclosure relates to a method for producing a dried solid, and a dried solid.
Background Art
[0002] Approximately 40% of the radiant energy of sunlight is accounted for by infrared rays. Infrared rays are called heat rays due to their high thermal effect. It is known that window materials used in office buildings, automobiles and the like that are required to have transparency generally transmit heat rays well, leading to a rise in the temperature inside rooms or vehicles.
[0003] Accordingly, for the purpose of energy saving, imparting a function of reflecting or absorbing heat rays to window materials has been studied. Examples of means for imparting a function of reflecting or absorbing heat rays (heat ray shielding property) to window materials include an infrared absorbing film containing tin-doped indium oxide (ITO) fine particles, antimony-doped tin oxide (ATO) fine particles, cesium tungstate and the like, and a method for attaching the same to window glass has been proposed.
[0004] Antimony and cesium are both toxic, and indium is a rare metal with high cost, so alternative materials for these materials are strongly desired. In addition, if the added amount of inorganic fine particles having heat ray shielding property is increased to lower the solar transmittance in order to enhance the heat ray shielding property, the visible light transmittance is similarly lowered. Conversely, if the visible light transmittance is increased to take in external light, there is a problem that the solar transmittance rises and the heat ray shielding property is lowered.
[0005] To address such problems, Patent Document 1 discloses, as a heat ray absorber with low environmental load and low cost, a heat ray absorber comprising sulfated cellulose nanocrystals represented by the following Chemical Formula 1 obtained from fibrous cellulose having a fiber width in the range of 3 nm to 1500 nm, and polythiophene doped with the sulfated cellulose nanocrystals, and a method for producing the same.
Chemical Formula
[0006] R shown in chemical formula 1 1 ~R 6 Each of these independently represents a hydrogen atom, a sulfonic acid group, or an alkyl sulfonic acid group with 1 to 6 carbon chains, and R 1 ~R 6 At least one of the groups is a sulfonic acid group or an alkyl sulfonic acid group with 1 to 6 carbon chains. Also, in chemical formula 1, n indicates a repetition of the group in parentheses. [Prior art documents] [Patent Documents]
[0007] [Patent Document 1] Japanese Patent Publication No. 2020-111747 [Overview of the project] [Problems that the invention aims to solve]
[0008] The manufacturing method described in Patent Document 1 produces a heat-absorbing material dispersed in water. From the viewpoint of reducing the cost of transporting and storing the heat-absorbing material, it is advantageous to dry and remove the water to obtain a dry solid of the heat-absorbing material, transport and / or store the dry solid, mix the dry solid with water to disperse (i.e., redisperse) the heat-absorbing material in water, and use the resulting dispersion (i.e., redispersed liquid) to manufacture products such as infrared-absorbing films. However, according to the inventors' research, the heat-absorbing material disclosed in Patent Document 1 undergoes hydrogen bonding and polythiophene crystallization during the drying process, making it difficult to redisperse the heat-absorbing material in water to exhibit its original heat-absorbing properties.
[0009] Therefore, one object of this disclosure is to provide a method for producing a dry solid containing a composite having heat-absorbing properties, wherein the composite can be redispersed in water and the redispersed composite can exhibit good heat-absorbing properties. Another object of this disclosure is to provide a dry solid containing a composite having heat-absorbing properties, wherein the composite can be redispersed in water and the redispersed composite can exhibit good heat-absorbing properties. [Means for solving the problem]
[0010] The forms of this disclosure include the following: [Aspect 1] A method for producing a dry solid containing a complex comprising sulfated polysaccharides and polythiophene, Separating the solid phase from the dispersion of the complex containing the sulfated polysaccharide and the polythiophene, The solid phase is dried to obtain the dried solid having a water content of 15 wt% or more. Methods that include... [Aspect 2] The method according to embodiment 1, wherein the dispersion of the composite comprises water and an organic solvent as a dispersion medium. [Aspect 3] The method according to embodiment 1 or 2, wherein the moisture content of the dry solid is 30 wt% or less. [Aspect 4] The method according to any one of embodiments 1 to 3, wherein the dried solid is obtained by drying the solid phase at a temperature of 60°C or lower. [Aspect 5] The method according to any one of embodiments 1 to 4, wherein separating the solid phase from the dispersion includes at least one of filtration or sedimentation of the dispersion. [Aspect 6] The method according to embodiment 5, wherein separating the solid phase from the dispersion includes centrifuging the dispersion. [Aspect 7] The method according to any one of embodiments 1 to 6, wherein the dispersion of the complex is prepared without undergoing dialysis. [Aspect 8] The method according to any one of embodiments 1 to 7, wherein the sulfated polysaccharide is at least one selected from the group consisting of amorphous sulfated polysaccharides and sulfated esterified fine cellulose fibers. [Aspect 9] The method according to embodiment 8, wherein the amorphous sulfated polysaccharide is at least one selected from the group consisting of a sulfated polysaccharide represented by the following formula (1), a sulfated polysaccharide represented by the following formula (2), carrageenan, sacran, rhamnan sulfate, fucoidan, chondroitin sulfate, porphyran, funoran, dermatan sulfate, and heparin. [ka] (In formulas (1) and (2), R is independently either a hydrogen atom or a group represented by formula (3), where at least one of the Rs in parentheses is a group represented by formula (3), and n represents the degree of polymerization.) [ka] (In formula (3), X is a hydroxyl group or -O - (M m+ ) 1 / m And M m+ (where m is an m-valence cation, m is 1, 2, or 3, and the wavy line indicates a bond site with another atom.) [Aspect 10] The method according to embodiment 9, wherein the amorphous sulfated polysaccharide is carrageenan. [Aspect 11] The method according to embodiment 10, wherein the amorphous sulfated polysaccharide is at least one selected from the group consisting of lambda-carrageenan, kappa-carrageenan, and iota-carrageenan. [Aspect 12] It contains a complex comprising sulfated polysaccharides and polythiophenes. A dry solid having a moisture content of 15 wt% or more. [Aspect 13] The dried solid according to embodiment 12, wherein the moisture content of the dried solid is 30 wt% or less. [Aspect 14] The dry solid according to aspect 12 or 13, wherein in an aqueous dispersion prepared by adding 1 part by weight of the dry solid to 999 parts by weight of ion-exchanged water, the complex is in the form of particles having a median diameter D50 in the range of 20 nm to 120 nm. [Aspect 15] The dry solid according to any one of aspects 12 to 14, wherein the sulfated polysaccharide is at least one selected from the group consisting of amorphous sulfated polysaccharides and sulfated fine cellulose fibers. [Aspect 16] The dry solid according to aspect 15, wherein the amorphous sulfated polysaccharide is at least one selected from the group consisting of a sulfated polysaccharide represented by the following formula (1), a sulfated polysaccharide represented by the following formula (2), carrageenan, xanthan gum, rhamnan sulfate, fucoidan, chondroitin sulfate, porphyran, funoran, dermatan sulfate, and heparin. [Chemical Formula] (In formulas (1) and (2), R each independently represents a hydrogen atom or a group represented by formula (3), provided that at least one R in the parentheses is a group represented by formula (3), and n represents the degree of polymerization.) [Chemical Formula] (In formula (3), X is a hydroxy group or -O - (M m+ ) 1 / m , M m+ is an m-valent cation, m is 1, 2, or 3, and the wavy line represents the bonding site to other atoms.) [Aspect 17] The dry solid according to aspect 16, wherein the amorphous sulfated polysaccharide is carrageenan. [Aspect 18] The dry solid according to aspect 17, wherein the amorphous sulfated polysaccharide is at least one selected from the group consisting of lambda-carrageenan, kappa-carrageenan, and iota-carrageenan. [Aspect 19] A dry solid produced by the method according to any one of aspects 1 to 11. [Effects of the Invention]
[0011] By mixing the dried solid obtained by the manufacturing method of this disclosure or the dried solid of this disclosure with water, the composite having heat-absorbing properties can be redispersed in water. The redispersed composite can exhibit good heat-absorbing properties. [Modes for carrying out the invention]
[0012] The embodiments described below are not limited to those described herein. Various modifications, changes, additions, omissions, and / or combinations of the embodiments described below are possible without departing from the technical scope set forth in the claims.
[0013] In this application, a numerical range represented by the symbol "~" includes the numerical values before and after the symbol "~" as the lower and upper limits, respectively, unless otherwise specified. The upper and lower limits described in this application may be used individually or in any combination.
[0014] In this application, "containing" and "containing" mean that additional components or elements may be included unless otherwise specified, and encompass "essentially made of" and "consisting of." "Essentially made of" means that additional components or elements may be included that do not substantially adversely affect the product. "Consisting of" means that only the described material or element is included, but does not exclude the inclusion of unavoidable impurities.
[0015] In this application, the term "and / or" refers to at least one of the listed items and all possible combinations thereof.
[0016] (1)Dry solid One embodiment of the dried solid contains a complex comprising sulfated polysaccharides and polythiophene, and has a water content of 15 wt% or more.
[0017] (sulfated polysaccharide) Sulfated polysaccharides are polysaccharides having sulfate ester groups as substituents. The sulfate ester group content of sulfated polysaccharides is not particularly limited, but may be, for example, 1.0 mmol / g to 6.0 mmol / g, 2.0 mmol / g to 5.0 mmol / g, 2.2 mmol / g to 4.8 mmol / g, or 2.5 mmol / g to 4.6 mmol / g. When the sulfate ester group content is within the above range, the sulfated polysaccharide can promote the dispersion of polythiophene, and the spacing of the sulfate ester groups is appropriate. The sulfate ester group content can be determined by combustion absorption-ion chromatography (IC) (combustion absorption-IC method, combustion IC method).
[0018] The sulfated polysaccharide may be at least one selected from the group consisting of amorphous sulfated polysaccharides and sulfated esterified fine cellulose fibers.
[0019] Amorphous sulfated polysaccharides do not include crystalline sulfated polysaccharides such as sulfated esterified cellulose. In this disclosure, amorphous means that the degree of crystallinity of type I cellulose, calculated by formula 1 below based on the diffraction intensity measurement results using an X-ray diffractometer, is less than 5%. Cellulose type I crystallinity (%) = [(I 200 -I am ) / I 200 ] × 100 … Formula 1 Here, I 200 This shows the X-ray diffraction intensity at 2θ = 22.6°, and I am This shows the X-ray diffraction intensity at 2θ = 18.5°.
[0020] The amorphous sulfated polysaccharides are not particularly limited, but may be at least one selected from, for example, the sulfated polysaccharide represented by formula (1) below, the sulfated polysaccharide represented by formula (2) below, carrageenan, sacran, rhamnan sulfate, fucoidan, chondroitin sulfate, porphyran, funoran, dermatan sulfate, and heparin. [ka] (In formulas (1) and (2), R is independently either a hydrogen atom or a group represented by formula (3) below, provided that at least one of the Rs in parentheses is the group represented by formula (3).) [ka] (In formula (3), X is a hydroxyl group or -O - (M m+ ) 1 / m And M m+ (where m is an m-valence cation, m is 1, 2, or 3, and the wavy line indicates a bond site with another atom.)
[0021] In equations (1) and (2), n represents the degree of polymerization. n may be 100 or more, 100 to 10000, 300 to 5000, or 500 to 2000. When the degree of polymerization is within the above range, the dispersion of the composite may have an appropriate viscosity.
[0022] The group represented by formula (3) can bond with an oxygen atom at the bonding site to form a sulfate ester group.
[0023] In equation (3), when m is 1, M m+ is one -SO3 - It forms an ionic bond with m. When m is 2 or 3, M m+ is 2 or 3 -SO3 - An ionic bond is formed between them. m is preferably 1.
[0024] M m+ This may be a metal ion or an ammonium ion. The metal ion may be an alkali metal ion, an alkaline earth metal ion, a transition metal ion, or another metal ion.
[0025] Examples of alkali metal ions include lithium ions (Li + ), sodium ions (Na + ), potassium ions (K + ), rubidium ion (Rb + ), and cesium ions (Cs +Examples of alkaline earth metal ions include calcium ions (Ca 2+ ) and strontium ions (Sr 2+ Examples of transition metal ions include iron ions, nickel ions, palladium ions, copper ions, and silver ions. Examples of other metal ions include beryllium ions, magnesium ions, zinc ions, and aluminum ions.
[0026] Ammonium ions are NH4 + , or NH4 + This can be an ammonium ion derived from various amines in which one or more hydrogen atoms are replaced by an organic group. An example of an ammonium ion is NH4. + Examples include quaternary ammonium cations, alkanolamine ions, and pyridinium ions.
[0027] M m+ From the viewpoint of the viscosity of the aqueous dispersion, this may be sodium ions, potassium ions, calcium ions, or quaternary ammonium cations, or it may be sodium ions, potassium ions, or calcium ions, or it may be sodium ions.
[0028] In formula (3), X is a hydroxyl group or -O - M + It may be a hydroxyl group or -O - Na + That's fine.
[0029] The base represented by formula (3) may have only one type of X or two or more types.
[0030] The amorphous sulfated polysaccharide may be carrageenan, and in particular, at least one selected from the group consisting of lambda-carrageenan, kappa-carrageenan, and iota-carrageenan.
[0031] Carrageenan can be extracted from red algae. Carrageenan has a structure in which D-galactose is linked by alternating α-1,3 or β-1,4 bonds. Carrageenan is classified into three types, kappa (κ), iota (ι), and lambda (λ), depending on the number of sulfate groups and the presence or absence of anhydro bonds, and any of these can be used as amorphous sulfated polysaccharides. That is, amorphous sulfated polysaccharides may be at least one selected from the group consisting of lambda-carrageenan, kappa-carrageenan, and iota-carrageenan. Carrageenan is commercially available, and it may be used as is or purified before use.
[0032] The content of sulfate ester groups in amorphous sulfated polysaccharides may be, for example, 2.0 mmol / g to 6.0 mmol / g, 2.0 mmol / g to 4.0 mmol / g, or 2.5 mmol / g to 3.5 mmol / g. When the content of sulfate ester groups is within the above range, the dispersion of polythiophene may be promoted.
[0033] The number of constituent monosaccharides in amorphous sulfated polysaccharides may be, for example, 200 or more, 200 to 20000, 600 to 10000, or 1000 to 4000. In the case of carrageenan and sulfated polysaccharides represented by formulas (1) and (2), since the constituent units are disaccharides, twice the degree of polymerization corresponds to the number of constituent monosaccharides. The number of constituent monosaccharides in amorphous sulfated polysaccharides can be calculated by dividing the number-average molecular weight, obtained by gel permeation chromatography using standard pullulan as the molecular weight standard, by the molecular weight of the monosaccharide.
[0034] Sulfate-esterified fine cellulose fibers have a substituent represented by the following formula (4). [ka] (In formula (4), Y is a hydroxyl group, -O - (M m+ ) 1 / m , or an alkyl group having 1 to 6 carbon atoms, M m+(where m is an m-valence cation, m is 1, 2, or 3, and the wavy line indicates a bond site with another atom.)
[0035] The group represented by formula (4) can bond with an oxygen atom at the bonding site to form a sulfate ester group.
[0036] Examples of alkyl groups having 1 to 6 carbon atoms include methyl group, ethyl group, n-propyl group, isopropyl group, n-butyl group, sec-butyl group, tert-butyl group, n-pentyl group, 2-methyl-butyl group, 3-methylbutyl group, 2-ethyl-propyl group, and n-hexyl group.
[0037] M in equation (4) m+ M in equation (3) m+ Since it is similar to [another example], the explanation will be omitted.
[0038] In formula (4), Y is preferably a hydroxyl group or -O - (M m+ ) 1 / m It may be, more preferably a hydroxyl group or -O - M + It may be a hydroxyl group or -O - Na + That's fine.
[0039] The group represented by formula (4) may have only one type of Y, or two or more types.
[0040] The sulfate ester group content of sulfated fine cellulose fibers may be, for example, 1.0 mmol / g to 6.0 mmol / g, 2.0 mmol / g to 5.5 mmol / g, 3.0 mmol / g to 5.0 mmol / g, or 3.1 mmol / g to 4.6 mmol / g. When the sulfate ester group content is within the above range, the sulfated polysaccharide can promote the dispersion of polythiophene, and the spacing of the sulfate ester groups is appropriate. The sulfate ester group content of sulfated fine cellulose fibers can be adjusted, for example, by controlling the concentration of reagents such as sulfuric acid in the solution used to defibrate the pulp (defibration solution), the amount of pulp relative to the defibration solution, the reaction time, and / or the reaction temperature.
[0041] The average degree of polymerization of the sulfated cellulose constituting the sulfated esterified fine cellulose fibers may be less than 1500, 200-700, 220-600, or 240-500. When the average degree of polymerization is within the above range, the sulfated esterified fine cellulose fibers can contribute to improving the degree of polymerization of polythiophene while maintaining good dispersibility. The average degree of polymerization of sulfated esterified cellulose is measured by the viscosity method. Specifically, sulfated esterified fine cellulose fibers are dissolved in a 0.5 M copper ethylenediamine solution, and the resulting solution is kept warm at 25°C before measuring the viscosity of the solution using a Cannon-Fenske kinematic viscosity tube. The average degree of polymerization is calculated using the following formula, with η being the viscosity of the solution and η0 being the viscosity of the 0.5 M copper ethylenediamine solution. Intrinsic viscosity [η]=(η / η0) / {c(1+A×η / η0)} (In the formula, c is the concentration of sulfated esterified fine cellulose fibers (g / dL) at the time of viscosity measurement, and A is a value specific to the type of solution; in the case of a 0.5 M copper ethylenediamine solution, A = 0.28.) Average degree of polymerization DP=[η] / aK (In the formula, a and K are values determined by the type of polymer and solvent; in the case of cellulose dissolved in copper ethylenediamine, K = 5.7 × 10) -3 (where a=1.)
[0042] Common cellulose (unmodified cellulose) is a polysaccharide in which glucose is linked by β-1,4-glycosidic bonds, (C6H 10 O5) n It is represented by (4). Sulfate-esterified fine cellulose fibers substituted with the group represented by formula (4) are composed of modified cellulose.
[0043] The average fiber width of the sulfated fine cellulose fibers may be 1 nm to 1000 nm, 1 nm to 100 nm, or 2 nm to 10 nm. The average fiber length of the fine cellulose fibers is not particularly limited, but may be 0.1 μm to 6 μm or 0.1 μm to 2 μm. The average fiber width and average fiber length can be measured, for example, by using an atomic force microscope (SPM-9700HT, manufactured by Shimadzu Corporation) to measure the fiber width (fiber diameter (equivalent to a circle diameter)) and fiber length of 50 arbitrarily selected fibers, and then taking the average value of each. The average fiber width and average fiber length can be adjusted to a desired range, for example, by controlling the sulfated esterification reaction time and / or the mixing ratio of reagents.
[0044] In sulfated fine cellulose fibers, typically some of the OH groups in the cellulose constituting the fiber are replaced with sulfated ester groups. Sulfated fine cellulose fibers can be produced, for example, by sulfated esterification and defibrillation of raw pulp.
[0045] Sulfate-esterified fine cellulose fibers may further have substituents other than the sulfate ester group (hereinafter referred to as "other substituents"). These other substituents typically substitute for at least one of the OH groups in the cellulose constituting the fine cellulose fibers. Examples of other substituents include anionic substituents and their salts, ester groups, ether groups, acyl groups, aldehyde groups, alkyl groups, alkylene groups, aryl groups, and combinations of two or more of these. From the viewpoint of nanodispersibility, the other substituents are preferably anionic substituents or their salts, acyl groups, or combinations of two or more of these. Examples of preferred anionic substituents include carboxyl groups, phosphate ester groups, phosphite ester groups, and xantate groups. Examples of preferred salts of anionic substituents include sodium salts, potassium salts, and calcium salts. An example of a preferred acyl group is the acetyl group.
[0046] (Polythiophene) Polythiophenes typically have monomer units that have a thiophene skeleton. A monomer unit refers to a monomer-derived constituent unit that makes up a polythiophene, and is considered a repeating unit of the polythiophene. It is preferable that polythiophenes have monomer units (repeating units) represented by the following formula (5). [ka] (In formula (5), R 7 and R 8 Each of these independently represents a hydrogen atom, a linear or branched alkyl group having 1 to 8 carbon atoms, or a linear or branched alkoxy group having 1 to 8 carbon atoms, or R 7 and R 8 These elements are linked together to form a dioxyalkylene group with 1 to 8 carbon atoms, an aromatic ring, or a 3 to 7-membered alicyclic ring, where n represents the number of repeating units.
[0047] In equation (5), R 7 and R 8 Each of these may independently represent a linear or branched alkyl group having 1 to 6 carbon atoms.
[0048] In equation (5), R 7 and R 8 Each of these may independently represent a linear or branched alkoxy group having 1 to 6 carbon atoms.
[0049] In equation (5), R 7 and R 8 These may be linked together to form a dioxyalkylene group having 1 to 6 or 2 to 4 carbon atoms.
[0050] In equation (5), R 7 and R 8 R 7 and R 8 It may form a benzene ring together with the carbon atom to which it is bonded.
[0051] In equation (5), R 7 and R 8 These may be linked together to form a 4-7 member or 5-6 member alicyclic ring.
[0052] In equation (5), the value of n is not particularly limited, but it may be, for example, between 2 and 50. The larger n is, the more likely it is that the properties of polythiophene, such as its heat-shielding properties, will improve.
[0053] The repeating unit represented by formula (5) is derived from the monomer (thiophene) represented by formula (6). [ka] (In formula (6), R 7 and R 8 Each of these independently represents a hydrogen atom, a linear or branched alkyl group having 1 to 8 carbon atoms, or a linear or branched alkoxy group having 1 to 8 carbon atoms, or R 7 and R 8 These link together to form a dioxyalkylene group having 1 to 8 carbon atoms, an aromatic ring, or an alicyclic ring with 3 to 7 members.
[0054] In equation (6), R7 and R 8 Each independently represents a linear or branched alkyl group having 1 to 8 carbon atoms or a linear or branched alkoxy group having 1 to 8 carbon atoms, or R 7 and R 8 These may be linked together to form a dioxyalkylene group having 1 to 8 carbon atoms.
[0055] Examples of thiophenes represented by formula (6) include 3,4-dialkylthiophene, 3,4-dialkoxythiophene, and 3,4-alkylenedioxythiophene. Among these, 3,4-alkylenedioxythiophene is preferred.
[0056] More specific examples of thiophenes represented by formula (6) include 3,4-dihexylthiophene, 3,4-diethylthiophene, 3,4-dipropylthiophene, 3,4-dimethoxythiophene, 3,4-diethoxythiophene, 3,4-dipropoxythiophene, 3,4-dibutoxythiophene, 3,4-methylenedioxythiophene, 3,4-ethylenedioxythiophene, and 3,4-propylenedioxythiophene. Among these, 3,4-ethylenedioxythiophene (hereinafter sometimes abbreviated as EDOT) is preferred.
[0057] Specific examples of polythiophenes represented by formula (5) include poly(3,4-dihexylthiophene), poly(3,4-diethylthiophene), poly(3,4-dipropylthiophene), poly(3,4-dimethoxythiophene), poly(3,4-diethoxythiophene), poly(3,4-dipropoxythiophene), poly(3,4-dibutoxythiophene), poly(3,4-methylenedioxythiophene), poly(3,4-ethylenedioxythiophene), and poly(3,4-propylenedioxythiophene). Among these, poly(3,4-ethylenedioxythiophene), also abbreviated as PEDOT, is preferred.
[0058] (dry solid) The dried solid contains a composite material comprising sulfated polysaccharides and polythiophene. This composite material does not contain materials with a high environmental impact and possesses excellent heat absorption properties. The mass ratio of sulfated polysaccharides and polythiophene in the composite material is not particularly limited and may be adjusted as appropriate.
[0059] The dry solid contains water in addition to the composite. The water content of the dry solid is 15 wt% or more. This allows the composite to maintain a dispersed state without agglomeration for a long period of time in the dispersion (redispersion) of the composite prepared by mixing the dry solid with water. In other words, the dry solid can have good redispersibility in water. The water content of the dry solid may be 30 wt% or less. The water content of the dry solid may be 15 wt% to 30 wt% or 15 wt% to 25 wt%.
[0060] In an aqueous dispersion (redispersion) prepared by adding 1 part by weight of a dry solid to 999 parts by weight of deionized water, the composite may have particle forms with a median diameter D50 in the range of 20 nm to 120 nm, 25 nm to 100 nm, 30 nm to 80 nm, or 37 nm to 60 nm. In this case, the composite can maintain a dispersed state in the aqueous dispersion without agglomerating for a long period of time.
[0061] When a dry solid is mixed with water to prepare an aqueous dispersion (redispersion) containing the complex at a concentration of 0.01 wt%, the aqueous dispersion can have absorbances of 0.040-0.200, 0.045-0.150, 0.050-0.100, or 0.060-0.090 at a wavelength of 400 nm. Furthermore, the aqueous dispersion can have absorbances of 0.200-0.800, 0.220-0.700, 0.240-0.600, 0.250-0.500, or 0.260-0.400 at a wavelength of 1200 nm. The value obtained by dividing the absorbance of the aqueous dispersion at 1200 nm by the absorbance at 400 nm may be 3.5 or greater, 4.0 or greater, or 4.5 or greater. A higher value obtained by dividing the absorbance at 1200 nm by the absorbance at 400 nm indicates superior heat absorption properties of the composite. While there is no particular upper limit to this value, it is typically 8.0 or less. Composites possessing these characteristics have excellent heat absorption properties and can therefore be used as materials for products such as heat-absorbing films.
[0062] As described above, by mixing the dry solid according to the embodiment with water, the composite can be redispersed in water, and the redispersed composite can exhibit good heat absorption properties. Therefore, the composite containing sulfated polysaccharides and polythiophene can be stored and / or transported in the form of the dry solid according to the embodiment and subsequently used in the manufacture of products. Thus, the dry solid according to the embodiment contributes to reducing the cost of transporting and / or storing the composite containing sulfated polysaccharides and polythiophene, which are heat absorbers.
[0063] The dried solid may further contain other components (e.g., inorganic or organic additives).
[0064] Inorganic additives may be, for example, inorganic fine particles. Examples of inorganic fine particles include fine particles of silica, mica, talc, clay, carbon, carbonates (e.g., calcium carbonate, magnesium carbonate), oxides (e.g., aluminum oxide, titanium oxide, zinc oxide, iron oxide), ceramics (e.g., ferrite), or mixtures thereof. The dry solid may contain inorganic fine particles in an amount ranging from 0.09 wt% to 5 wt%.
[0065] Examples of organic additives include functional compounds such as dyes, UV absorbers, antioxidants, antistatic agents, and surfactants. The dried solid may contain organic additives in amounts ranging from 0.09 wt% to 5 wt%.
[0066] (2) Method for producing a dry solid A method for producing a dried solid according to one embodiment includes separating a solid phase from a dispersion of a complex containing sulfated polysaccharides and polythiophene, and drying the solid phase to obtain a dried solid having a water content of 15 wt% or more. This method can be used to produce the dried solid according to the above embodiment.
[0067] (Preparation of the complex dispersion) A dispersion of a complex containing sulfated polysaccharides and polythiophene can be prepared as follows.
[0068] Thiophene is oxidatively polymerized in the presence of sulfated polysaccharides, a solvent, and an oxidizing agent. Specifically, sulfated polysaccharides are dispersed in a dispersion medium (e.g., water) to prepare a dispersion, to which thiophene and an oxidizing agent are added to polymerize the thiophene and produce polythiophene. This yields a dispersion in which a complex containing sulfated polysaccharides and polythiophene is dispersed in the dispersion medium. While we do not wish for a restrictive interpretation, it is thought that in the complex, the polythiophene is doped with anions from the sulfated polysaccharides.
[0069] The oxidizing agent (hereinafter sometimes referred to as the polymerization initiator) is not particularly limited as long as it enables oxidative polymerization of thiophene. Examples of oxidizing agents include peroxodisulfate, sodium peroxodisulfate, potassium peroxodisulfate, ammonium peroxodisulfate, inorganic ferric oxide, organic ferric oxide, hydrogen peroxide, potassium permanganate, potassium dichromate, alkali perborate, iron(III) sulfate, and iron(III) chloride. Among these, peroxodisulfate, sodium peroxodisulfate, potassium peroxodisulfate, ammonium peroxodisulfate, iron(III) sulfate, and iron(III) chloride are preferred. These oxidizing agents may be used individually or in combination of two or more.
[0070] The amount of oxidizing agent used is not particularly limited, but for example, it may be in the range of 0.1 to 5 equivalents or 0.3 to 2 equivalents per mole of thiophene.
[0071] The amount of thiophene added per mole of monosaccharide constituting the sulfated polysaccharide can be adjusted as appropriate, but may be in the range of, for example, 0.5 moles to 3.0 moles or 0.7 moles to 2.0 moles.
[0072] As the dispersion medium, a medium capable of polymerization of thiophene should be used. Examples of usable dispersion media include aqueous solvents, particularly water. As the dispersion medium, an aqueous solvent may be used, which is a mixture of water and a lower alcohol (e.g., methanol and / or ethanol) or a polar organic solvent (e.g., acetone and / or acetonitrile). These solvents may be used individually or in combination of two or more.
[0073] The amount of solvent is not particularly limited, but may be in the range of 1,000 ml to 50,000 ml or 10,000 ml to 40,000 ml per mole of thiophene.
[0074] The time and temperature of the polymerization reaction may be set appropriately depending on the type of thiophene and sulfated polysaccharide used as the starting compounds, the type of oxidizing agent, etc. The polymerization reaction temperature may be, for example, in the range of 5°C to 90°C or 10°C to 80°C. The polymerization reaction time may be, for example, in the range of 1 hour to 96 hours or 3 hours to 48 hours.
[0075] A dispersion of the composite, containing water and an organic solvent as a dispersion medium, may be prepared by adding an organic solvent to the dispersion obtained after the polymerization reaction. This reduces the energy required for the solid phase drying step described later. Examples of suitable organic solvents include alcohols such as 2-propanol, methanol, ethanol, 1-butanol, 2-butanol, isobutanol, and t-butanol, as well as acetone, ethylene glycol, propylene glycol, and acetonitrile.
[0076] (Separation of solid phase from dispersion) The solid phase is separated from the dispersion of the composite prepared as described above. The solid phase can be separated by at least one of the following methods: filtration such as natural filtration, vacuum filtration, pressure filtration, or centrifugal filtration, or sedimentation separation such as centrifugation. In particular, the solid phase may be separated from the dispersion by centrifugal filtration.
[0077] The separated solid phase may be added back to the solvent to disperse the complex, and the solid phase may be separated one or more times by filtration or sedimentation. This allows for the removal of impurities such as oxidizing agents from the dispersion. Since impurities in the dispersion can be removed during the process of separating the solid phase from the dispersion, the dispersion may be prepared without purification by dialysis or the like. The solvent used for redispersing the separated solid phase may be an organic solvent. Examples of suitable organic solvents include alcohols such as 2-propanol, methanol, ethanol, 1-butanol, 2-butanol, isobutanol, and t-butanol, as well as acetone, ethylene glycol, propylene glycol, and acetonitrile.
[0078] (Drying of the solid phase) As described above, the recovered solid phase is dried to obtain a dried solid with a moisture content of 15 wt% or more. The moisture content of the dried solid can be controlled by drying conditions such as drying time, temperature, and pressure. For example, by drying the recovered solid phase at a temperature of 60°C or lower, a dried solid with a moisture content of 15 wt% or more can be obtained. The moisture content of the dried solid may be 15 wt% to 30 wt% or 15 wt% to 25 wt%.
[0079] Furthermore, a dry solid containing the composite can also be obtained by drying a dispersion of the composite, purified by dialysis or the like, to remove the dispersion medium. However, obtaining a dry solid by drying the solid phase recovered from the dispersion requires less energy. In addition, when obtaining a dry solid by drying the solid phase recovered from the dispersion, the entire solid phase is dried uniformly, resulting in a powdery, easy-to-handle dry solid.
[0080] (3) Uses of dry solids The dried solid according to this embodiment can be used in the manufacture of heat-absorbing products such as heat-absorbing films.
[0081] For example, a heat-absorbing film in which the composite is dispersed in a polymer matrix can be produced by adding a dry solid to an aqueous resin solution or an aqueous resin emulsion to prepare a coating solution containing a composite containing sulfated polysaccharides and polythiophene, as well as a polymer, and then applying the coating solution to a substrate and drying it.
[0082] Examples of polymers include vinyl acetate-polyvinyl alcohol copolymer, polypropylene glycol, polyethylene glycol, polyvinyl alcohol, polyvinyl alcohol-ethylene copolymer, polyvinyl alcohol-butenediol copolymer, polyethylene-vinyl acetate copolymer, cellulose monoalkylate (alkyl group has 1 to 18 carbon atoms), cellulose diarylate (alkyl group has 1 to 18 carbon atoms), cellulose trial chelate (alkyl group has 1 to 18 carbon atoms), polyethylene, polypropylene, polystyrene, polyalkyl (alkyl group has 1 to 18 carbon atoms) (meth)acrylate, carboxymethylcellulose sodium, cellulose alkyl ether Examples include hydroxyalkylates (alkyl groups have 1 to 18 carbon atoms), polyethylene terephthalate, polyethylene naphthalate, polyacrylamide and its derivatives, poly(meth)acrylic acid, polyvinyl chloride, cellulose, starch, gelatin, pullulan, dextran, hydroxyalkylene (meth)acrylate (alkyl groups have 1 to 18 carbon atoms), polyurethane, nylon-6,6, nylon-6, nylon-6,10, polyvinyl alkylal (alkyl groups have 1 to 18 carbon atoms), polyimide, syndiotactic 1,2-polybutadiene, 1,4-polybutadiene, polyisoprene, polystyrene-butadiene copolymer, ABS resin, phenolic resin, siloxane polymer, and silsesquioxane.
[0083] The thickness of the heat-absorbing film is not particularly limited, but may be, for example, 0.1 μm to 10,000 μm, 1 μm to 1,000 μm, or 5 μm to 100 μm.
[0084] The method for applying the coating solution to the substrate is not particularly limited, but examples include spray coating, spin coating, air knife coating, curtain coating, blade coating, dip coating, casting, two-roll coating, gate roll press, roll coating, bar coating, die coating, gravure, mist, printing, and inkjet.
[0085] The drying method is not particularly limited, but examples include natural drying, heat drying, freeze-drying, reduced-pressure drying, hot air drying, hot-pressure drying, infrared drying, and supercritical drying. The drying temperature may be set appropriately depending on the material and drying method, for example, 50°C to 250°C, 60°C to 150°C, or 80°C to 120°C. By setting the drying temperature to 250°C or lower, it is possible to prevent or suppress the decrease in the heat absorption properties of the composite during drying. Also, by setting the drying temperature higher, it is possible to shorten the drying time or improve the quality of the formed film.
[0086] As the substrate, for example, a glass plate, or a plastic sheet or film can be used. Examples of plastics include polyester, polyethylene, polypropylene, polystyrene, polyimide, poly(meth)acrylic ester, polyamide, polyethylene terephthalate, polyethylene naphthalate, epoxy resin, chlorine-based resin, silicone-based resin, phenolic resin, and mixtures thereof. [Examples]
[0087] The present disclosure will be specifically described below with reference to examples, but the present disclosure is not limited to these examples.
[0088] (1) Material The following sulfated polysaccharides were used in the examples. Carrageenan 1: Kappa-Carrageenan (manufactured by Taisho Technos Co., Ltd.) Carrageenan 2: Iota-Carrageenan (manufactured by Taisho Technos Co., Ltd.) Carrageenan 3: Lambda-Carrageenan (manufactured by Taisho Technos Co., Ltd.) Carrageenan 4: Iota-Carrageenan (manufactured by Takaragen Co., Ltd.) Carrageenan 5: Iota-Carrageenan (manufactured by Sansho Co., Ltd.) Sulfated cellulose fiber (S-CNF) 1: S-CNF synthesized in the following synthesis example 1 Sulfated cellulose fiber (S-CNF) 2: S-CNF synthesized in Synthesis Example 2 below
[0089] (2) Synthesis of sulfated fine cellulose fibers (S-CNF) [Synthesis Example 1] 150 g of DMSO, 16.5 g of acetic anhydride, and 3.2 g of 98% sulfuric acid were placed in a 300 ml sample bottle and stirred for approximately 30 seconds using a magnetic stirrer at room temperature of 23°C to prepare a defibrillated solution.
[0090] Next, 5.0 g of coniferous kraft pulp NBKP (manufactured by Nippon Paper Industries) was added to the defibration solution, and the mixture was stirred for a further 120 minutes at room temperature (23°C) to carry out the sulfuric acid esterification reaction. After stirring, 250 ml of distilled water was added to the defibration solution containing cellulose to stop the reaction, and then a 10% by mass aqueous sodium hydroxide solution was added until the pH reached 7 to neutralize the reaction solution. The supernatant was then removed by centrifugation to obtain the solids.
[0091] The solids were washed by adding 1350 ml of distilled water and 1350 ml of ethanol to the solids and stirring until uniformly dispersed, then removing the supernatant by centrifugation. The same procedure was repeated for a total of six washes. The centrifugation speed in each operation was 12000 rpm and the centrifugation time was 50 minutes. After washing, distilled water was added to the solids until the total weight was 1000 g, obtaining a heterogeneous mixture containing sulfated esterified fine cellulose fibers and water.
[0092] Next, the heterogeneous mixture was stirred for 3 minutes using a mixer (G5200, Biolomix) to obtain 1000 g of an aqueous dispersion in which 0.5% by mass of sulfated fine cellulose fibers were uniformly dispersed. Subsequently, the obtained aqueous dispersion of sulfated fine cellulose fibers was dried for 72 hours using a freeze dryer (FDU-2110, Tokyo Rikakikai) to obtain a dried sulfated fine cellulose fiber product.
[0093] 5 g of a dried sulfurized fine cellulose fiber was processed for 3 minutes in a dry pulverizer (Wonder Blender WB1, manufactured by Osaka Chemical Co., Ltd.) to obtain sulfurized cellulose fiber (S-CNF) 1, which is a sulfurized fine cellulose fiber powder.
[0094] [Synthesis Example 2] 5.0 g of coniferous kraft pulp NBKP (manufactured by Nippon Paper Industries) was added to 500 ml of N,N-dimethylformamide (DMF) and cooled to 10°C. 3.6 ml of chlorosulfonic acid was added dropwise to the DMF containing the coniferous kraft pulp NBKP over 60 minutes under a nitrogen atmosphere, and the mixture was stirred for 1 hour to obtain the reaction solution.
[0095] The reaction mixture was poured into 5000 ml of saturated sodium acetate solution, reprecipitation occurred, and the supernatant was removed by centrifugation to obtain the solid. The solid was washed once with a saturated ethanol solution of sodium acetate, and then washed with ethanol until the supernatant became neutral. The supernatant was then removed by centrifugation to obtain the solid, and distilled water was added to the solid until the total weight reached 1000 g, yielding a heterogeneous mixture containing sulfated esterified fine cellulose fibers and water.
[0096] Next, the heterogeneous mixture was stirred for 3 minutes using a mixer (G5200, Biolomix) to obtain 1000 g of an aqueous dispersion in which 0.5% by mass of sulfated fine cellulose fibers were uniformly dispersed. Subsequently, the obtained aqueous dispersion of sulfated fine cellulose fibers was dried for 72 hours using a freeze dryer (FDU-2110, Tokyo Rikakikai) to obtain a dried sulfated fine cellulose fiber product.
[0097] Next, 5 g of the dried sulfated esterified fine cellulose fiber was processed for 3 minutes in a dry pulverizer (Wonder Blender WB1, manufactured by Osaka Chemical Co., Ltd.) to obtain sulfated cellulose fiber (S-CNF)2, which is sulfated esterified fine cellulose fiber powder.
[0098] (3) Determination of sulfate ester group content of sulfated polysaccharides The sulfate ester group content of sulfated polysaccharides was quantified using the combustion absorption-IC method. Specifically, 0.01 g of dried sulfated polysaccharide was placed on a magnetic board and burned in a cyclic furnace at 1350°C under an oxygen atmosphere (flow rate: 1.5 L / min). The generated gas components were absorbed in 20 ml of 3% hydrogen peroxide solution. The resulting absorption solution was diluted to 100 ml with pure water, and the sulfate ion concentration (mass%) of the diluted solution was measured by ion chromatography. Based on the measurement results, the sulfate ester group content (mmol / g) per gram of sulfated polysaccharide was calculated. The results are shown in Table 1.
[0099] (4) Synthesis of the complex [Examples 1-15, Comparative Examples 1-10] 13.33 g of sulfated polysaccharides was added to deionized water to prepare a 653.33 g 2.0 wt% aqueous dispersion. 3.37 g of 3,4-ethylenedioxythiophene (EDOT) was added to this dispersion, and the EDOT was dispersed by internal ultrasonic irradiation for 1 minute. Next, 6.35 g of concentrated hydrochloric acid, 25.38 g of 0.48 g / L of iron(III) chloride hexahydrate aqueous solution, and 3.11 g of potassium peroxodisulfate were added, and the mixture was stirred at 40°C for 4 hours. After stirring, the mixture was added dropwise to 2100 g of 2-propanol and stirred for 15 minutes. The mixture was then filtered using a small centrifuge (H-112, manufactured by Kokusan Co., Ltd.) to recover the first filtration cake. The first filtration cake was added to 323 g of 2-propanol and stirred for 15 minutes. The mixture was then filtered using a small centrifuge (H-112, manufactured by Kokusan Co., Ltd.) to recover the second filtration cake. The second filtered cake was spread on a tray and placed in a vacuum constant-temperature dryer (manufactured by Tokyo Rikakikai Co., Ltd.), and dried under the conditions described in Table 1 to remove 2-propanol. This yielded 13.11 g of a dried solid of a complex of poly(3,4-ethylenedioxythiophene) (PEDOT) and sulfated polysaccharides (hereinafter referred to as "PEDOT / sulfated polysaccharide complex" as appropriate).
[0100] [Comparative Example 11] 1.33 g of carrageenan-2 was added to deionized water to prepare a 65.33 g 2.0 wt% aqueous dispersion. 0.337 g of 3,4-ethylenedioxythiophene (EDOT) was added, and the dispersion was irradiated with internal ultrasound for 1 minute to disperse the EDOT. Next, 0.635 g of concentrated hydrochloric acid, 2.538 g of 0.48 g / L of iron(III) chloride hexahydrate aqueous solution, and 0.311 g of ammonium peroxodisulfate were added, and the mixture was stirred at 40°C for 4 hours. After stirring, the mixture was placed in a dialysis cellulose tube (visking tube, molecular weight cutoff: approximately 3500, pore size: 1.25 nm) and stirred with 2000 g of deionized water. The deionized water was changed every 24 hours, and dialysis was performed for a total of 72 hours. This yielded an aqueous dispersion of a complex of PEDOT and carrageenan-2 (hereinafter referred to as "PEDOT / sulfated polysaccharide complex" as appropriate).
[0101] (5) Measurement of moisture content The moisture content of the dried solids of the PEDOT / sulfated polysaccharide complexes in Examples 1-15 and Comparative Examples 1-10 was measured using an electronic moisture meter (MOC63u, Shimadzu Corporation). Specifically, 1 g of the dried solid was heated at 120°C until the weight change rate over 30 seconds was 0.01% or less, and the moisture content of the dried solid was calculated from the weight loss. The results are shown in Table 1.
[0102] (6) Evaluation of redispersibility in water The redispersibility of the dried solids of the PEDOT / sulfated polysaccharide complexes from Examples 1-15 and Comparative Examples 1-10 in water was evaluated. Specifically, 1 part by weight of the dried solid was added to 999 parts by weight of deionized water, and the mixture was stirred by hand to prepare an aqueous dispersion of the complex with a concentration of 0.1 wt%. After the aqueous dispersion was allowed to stand for 72 hours, the dispersion state of the complex was visually confirmed. The results are shown in Table 1. In Table 1, A indicates that the complex was dispersed in water, and B indicates that the complex had aggregated.
[0103] (7) Measurement of absorbance of dispersion The dried solids of the PEDOT / sulfated polysaccharide complexes from Examples 1-15 or Comparative Examples 1-10 were added to deionized water and stirred to prepare an aqueous dispersion of the complex with a concentration of 0.01 wt%. The aqueous dispersion of the PEDOT / sulfated polysaccharide complex prepared in Comparative Example 11 was diluted with deionized water to prepare an aqueous dispersion of the complex with a concentration of 0.01 wt%. The absorbance of these 0.01 wt% aqueous dispersions was measured at 1 nm intervals in the wavelength range of 200 nm to 1800 nm using a UV-Vis-Near-Infrared spectrophotometer (JASCO v-770ST). The absorbance at 400 nm, the absorbance at 1200 nm, and the absorbance at 1200 nm divided by the absorbance at 400 nm (absorbance at 1200 nm / absorbance at 400 nm) are shown in Table 1. The value obtained by dividing the absorbance at a wavelength of 1200 nm by the absorbance at a wavelength of 400 nm represents the heat absorption characteristics of the composite.
[0104] (8) Measurement of particle size The particle size distribution of 1 part by weight of the dried solid of the PEDOT / sulfated polysaccharide complex from Examples 1-15 or Comparative Examples 1-10 in water was measured. Specifically, 1 part by weight of the dried solid was added to 999 parts by weight of deionized water and stirred to prepare a 0.1 wt% aqueous dispersion of the PEDOT / sulfated polysaccharide complex, and the particle size distribution of the complex in the aqueous dispersion was measured using a laser diffraction particle size distribution analyzer (Mastersizer 3000+, Malvern Panalytical). In addition, the aqueous dispersion of the PEDOT / sulfated polysaccharide complex prepared in Comparative Example 11 was diluted with deionized water to prepare a 0.1 wt% aqueous dispersion of the complex, and the particle size distribution of the complex in the aqueous dispersion was measured using the same laser diffraction particle size distribution analyzer. The median diameter D50 of the complex was determined from the particle size distribution. The results are shown in Table 1.
[0105] (9) Film production (9-1) Water-soluble resin film A 13.0 wt% resin aqueous solution was prepared by stirring 60 g of polyvinyl alcohol copolymer (RS-1717, manufactured by Kuraray Co., Ltd.) and 400 g of deionized water in a 1000 mL container at 100°C for 4 hours.
[0106] 1.30 g of the dried solid from Example 3 was added to 161.0 g of the resin aqueous solution, and then a surfactant solution prepared by dissolving 0.042 g of octylphenol ethoxylate (Triton X-100, manufactured by Nacalai Tesque Co., Ltd.) in 37.9 g of deionized water was added and the mixture was thoroughly stirred. A coating solution was then prepared.
[0107] A coating solution was applied to a polyester film (Lumirror® T60, manufactured by Toray Industries, Inc.) using a doctor blade to form a coating. The coating was dried at 90°C for 30 minutes to obtain a water-soluble resin film with a thickness of 10 μm and a composite content of 5 wt%. The film thickness was measured using a 3D measuring laser microscope (OLS5100, manufactured by Olympus Corporation).
[0108] (9-2) Water-based emulsion resin film 76.9 g of well-stirred urethane acrylate emulsion (UCECOAT 7200, manufactured by Daicel Ornex Co., Ltd., solid content concentration 65 wt%) was mixed with 3.09 g of the dried solid from Example 3, 2.00 g of photopolymerization initiator (IRGACURE 1173, manufactured by BASF) and 0.40 g of surface modifier (Surfinol 104E, manufactured by Nisshin Chemical Industry Co., Ltd.), and the mixture was thoroughly stirred. A coating solution was then prepared.
[0109] The coating solution was applied to a polyester film (Toray Industries, Inc.'s Lumirror® T60) using a doctor blade to form a coating. The coating was dried at 80°C for 10 minutes. The coating was then irradiated with an illuminance of 200 mW·cm using an ultraviolet irradiation device (iGraphics Co., Ltd.'s iGrantage ECS-401GX model). 2 , cumulative light intensity 800 mJ / cm 2 The coating was cured by irradiation with ultraviolet light. This resulted in an aqueous emulsion resin film with a thickness of 10 μm and a composite content of 5 wt%. The film thickness was measured using a 3D measuring laser microscope (OLS5100, manufactured by Olympus Corporation).
[0110] (9-3) Water-based inorganic-organic hybrid resin film 128.2 g of well-stirred polysiloxane / epoxysilane curable acrylic resin (CERANATE WSA-1070, manufactured by DIC Corporation, solid content concentration 39 wt%) was mixed with 3.09 g of the dried solid from Example 3, and 0.40 g of surface modifier (Surfinol 104E, manufactured by Nisshin Chemical Industry Co., Ltd.) was added and the mixture was thoroughly stirred. A coating solution was then prepared.
[0111] A coating solution was applied to a polyester film (Toray Industries, Inc.'s Lumirror® T60) using a doctor blade to form a coating. The coating was dried at 80°C for 10 minutes. This yielded an aqueous inorganic-organic hybrid resin film with a thickness of 10 μm and a composite content of 5 wt%. The film thickness was measured using a 3D measuring laser microscope (Olympus Corporation's OLS5100).
[0112] (10) Measurement of the absorbance of the film The absorbance of the fabricated water-soluble resin film, aqueous emulsion resin film, and aqueous inorganic-organic hybrid resin film was measured at 1 nm intervals in the wavelength range of 200 nm to 1850 nm using a UV-Vis-Near-Infrared spectrophotometer (JASCO Corporation v-770ST). Table 2 shows the absorbance at 400 nm, the absorbance at 1200 nm, and the value obtained by dividing the absorbance at 1200 nm by the absorbance at 400 nm (absorbance at 1200 nm / absorbance at 400 nm).
[0113] [Table 1]
[0114] [Table 2]
[0115] As shown in Table 1, the median diameter D50 of the particle size distribution measured after redispersing the dried solids of the PEDOT / sulfated polysaccharide complexes of Examples 1 to 15, which had a water content of 15.1 wt% to 22.3 wt%, in water was 39 to 55 nm, indicating that the complexes were dispersed without aggregation. The evaluation results of the redispersibility in water also showed that the dried solids of Examples 1 to 15 had good redispersibility in water.
[0116] On the other hand, the median diameter D50 of the particle size distribution measured after redispersing the dried solids of the PEDOT / sulfated polysaccharide complexes of Comparative Examples 1 to 10, which had a water content of 6.7 wt% to 14.1 wt%, in water was 166 to 2900 nm, which was much larger than that of Examples 1 to 15. This indicates that the complex aggregated in water and was not redispersed well. The evaluation results of the water redispersibility also showed that the water redispersibility of the dried solids of Comparative Examples 1 to 10 was insufficient.
[0117] Furthermore, Table 1 shows that the dried solids of Examples 1 to 15, which had a moisture content of 15.1 wt% to 22.3 wt%, could be obtained by drying the second filtration cake recovered by centrifugal filtration at a temperature of 60°C or lower.
[0118] When comparing the absorbance measurements of dispersions prepared by redispersing the dried solid PEDOT / sulfated polysaccharide complexes of Examples 1-15 in water with the absorbance measurements of the dispersion of the PEDOT / sulfated polysaccharide complex of Comparative Example 11, which was purified by dialysis, the absorbance values at 1200 nm and 400 nm were equivalent in both cases. This indicates that drying and redispersion of the PEDOT / sulfated polysaccharide complexes in Examples 1-15 do not lead to a deterioration of their heat absorption properties.
[0119] Table 2 shows that all films possessed excellent heat absorption properties.
Claims
1. A method for producing a dry solid containing a complex comprising sulfated polysaccharides and polythiophene, Separating the solid phase from the dispersion of the complex containing the sulfated polysaccharide and the polythiophene, The solid phase is dried to obtain the dried solid having a water content of 15 wt% or more. Methods that include...
2. The method according to claim 1, wherein the dispersion of the composite comprises water and an organic solvent as a dispersion medium.
3. The method according to claim 1 or 2, wherein the moisture content of the dry solid is 30 wt% or less.
4. The method according to claim 1 or 2, wherein the dried solid is obtained by drying the solid phase at a temperature of 60°C or lower.
5. The method according to claim 1 or 2, wherein separating the solid phase from the dispersion includes at least one of filtration or sedimentation of the dispersion.
6. The method according to claim 5, wherein separating the solid phase from the dispersion includes centrifuging the dispersion.
7. The method according to claim 1 or 2, wherein the dispersion of the complex is prepared without undergoing dialysis.
8. The method according to claim 1 or 2, wherein the sulfated polysaccharide is at least one selected from the group consisting of amorphous sulfated polysaccharides and sulfated esterified fine cellulose fibers.
9. The method according to claim 8, wherein the amorphous sulfated polysaccharide is at least one selected from the group consisting of a sulfated polysaccharide represented by the following formula (1), a sulfated polysaccharide represented by the following formula (2), carrageenan, sacran, rhamnan sulfate, fucoidan, chondroitin sulfate, porphyran, funoran, dermatan sulfate, and heparin. 【Chemistry 1】 (In formulas (1) and (2), R is independently either a hydrogen atom or a group represented by formula (3), provided that at least one of the Rs in parentheses is a group represented by formula (3), and n represents the degree of polymerization.) 【Chemistry 2】 (In formula (3), X is a hydroxyl group or -O - (M m+ ) 1/m And M m+ (where m is an m-valent cation, m is 1, 2, or 3, and the wavy line indicates a bond site with another atom.)
10. The method according to claim 9, wherein the amorphous sulfated polysaccharide is carrageenan.
11. The method according to claim 10, wherein the amorphous sulfated polysaccharide is at least one selected from the group consisting of lambda-carrageenan, kappa-carrageenan, and iota-carrageenan.
12. It contains a complex comprising sulfated polysaccharides and polythiophenes. A dry solid having a moisture content of 15 wt% or more.
13. The dried solid according to claim 12, wherein the moisture content of the dried solid is 30 wt% or less.
14. The dried solid according to claim 12 or 13, wherein in an aqueous dispersion prepared by adding 1 part by weight of the dried solid to 999 parts by weight of deionized water, the composite has the form of particles having a median diameter D50 in the range of 20 nm to 120 nm.
15. The dried solid according to claim 12 or 13, wherein the sulfated polysaccharide is at least one selected from the group consisting of amorphous sulfated polysaccharides and sulfated esterified fine cellulose fibers.
16. The dried solid according to claim 15, wherein the amorphous sulfated polysaccharide is at least one selected from the group consisting of a sulfated polysaccharide represented by the following formula (1), a sulfated polysaccharide represented by the following formula (2), carrageenan, sacran, rhamnan sulfate, fucoidan, chondroitin sulfate, porphyran, funoran, dermatan sulfate, and heparin. 【Transformation 3】 (In formulas (1) and (2), R is independently either a hydrogen atom or a group represented by formula (3), provided that at least one of the Rs in parentheses is a group represented by formula (3), and n represents the degree of polymerization.) 【Chemistry 4】 (In formula (3), X is a hydroxyl group or -O - (M m+ ) 1/m And M m+ (where m is an m-valent cation, m is 1, 2, or 3, and the wavy line indicates a bond site with another atom.)
17. The dried solid according to claim 16, wherein the amorphous sulfated polysaccharide is carrageenan.
18. The dried solid according to claim 17, wherein the amorphous sulfated polysaccharide is at least one selected from the group consisting of lambda-carrageenan, kappa-carrageenan, and iota-carrageenan.
19. A dried solid produced by the method described in claim 1 or 2.
Citation Information
Patent Citations
Heat ray absorption material and method for producing the same, and heat ray absorption film
JP2020111747A